Age of Both Parents Influences Reproduction and Egg Dumping Behavior in Drosophila melanogaster. (7th February 2019) - Mossman, Jim A; Mabeza, Russyan Mark S; Blake, Emma; Mehta, Neha; Rand, David M
Abstract: Trans-generational maternal effects have been shown to influence a broad range of offspring phenotypes. However, very little is known about paternal trans-generational effects. Here, we tested the trans-generational effects of maternal and paternal age, and their interaction, on daughter and son reproductive fitness in Drosophila melanogaster. We found significant effects of parent ages on offspring reproductive fitness during a 10 day postfertilization period. In daughters, older (45 days old) mothers conferred lower reproductive fitness compared with younger mothers (3 days old). In sons, father's age significantly affected reproductive fitness. The effects of 2 old parents were additive in both sexes and reproductive fitness was lowest when the focal individual had 2 old parents. Interestingly, daughter fertility was sensitive to father's age but son fertility was insensitive to mother's age, suggesting a sexual asymmetry in trans-generational effects. We found the egg-laying dynamics in daughters dramatically shaped this relationship. Daughters with 2 old parents demonstrated an extreme egg dumping behavior on day 1 and laid >2.35× the number of eggs than the other 3 age class treatments. Our study reveals significant trans-generational maternal and paternal age effects on fertility and an association with a novel egg laying behavioral phenotype in Drosophila.